61 THE LOSS OF LIMK1 PROTECTS ENDOTHELIAL BARRIER FUNCTION. (1st March 2006) - Gorovoy, M.; Neamu, R. F; Predescu, D.; Voyno-Yasenetskaya, T.
Abstract : Introduction: Acute lung injury (ALI) is a syndrome of acute respiratory failure that results from acute pulmonary edema and inflammation. The development of ALI is associated with direct pulmonary injury from pneumonia and aspiration as well as indirect pulmonary injury from trauma and sepsis. LIMK1 is a serine/threonine kinase that is involved in cytoskeleton dynamics. Methods: The role of LIMK1 in the regulation of endothelial permeability was evaluated using in vivo lung perfusion studies, transendothelial resistance of cell culture measurements, Western blotting, and electron and confocal microscopy. Results: As enhanced pulmonary vascular permeability is a hallmark of acute lung injury, we examined the lung microcirculation in LIMK1 knockout mice. We found that endothelial permeability in the lungs of LIMK1 -/- mice was lower than that of wild-type mice. Notably, the endothelial permeability of the lungs of LIMK1 -/- mice after PAR1 peptide perfusion was significantly lower than that of wild type. Down-regulation of endogenous LIMK1 with siRNA in HUVECs resulted in increased transendothelial resistance. The overexpression of w.t. LIMK1 in HUVECs led to the decreased transendothelial resistance and opening of tight junctions as was revealed by confocal microscopy with the staining for ZO-1 and VE-cadherin. To study endotoxin-induced acute lung injury, anesthetized mice received LPS (ip) and the wet to dry ratio of the lungs of wild-type mice was compared to that of LIMK1 -/- mice. We found a decreased edema formation in LIMK1 -/- mice upon LPS treatment. Conclusions: We suggest that the loss of LIMK1 protein leads to less permeable pulmonary blood vessels. These results favor the possibility that the inhibition of LIMK1 function may attenuate acute lung injury. This study was supported by NIH grants GM56159 and GM65160 and an American Heart Association (AHA) grant to T.V.Y. and an AHA predoctoral fellowship 0510133Z to M.G.